Kebijakan Sertifikasi Wakaf di Indonesia dalam Pembangunan Berkelanjutan: Peluang dan Tantangan - Aminuddin; wibowo, Wahyu; Choiri, Ahmad; Ariga, Adi; Satibi, Ibi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Abstract: Waqf is a unique Islamic economic instrument that functions to distribute social benefits sustainably. However, the management of waqf in Indonesia faces challenges, particularly related to certification that provides legal certainty over waqf assets. This certification is crucial for optimizing the utilization of assets and enhancing transparency and accountability in their management. Without certification, waqf assets are vulnerable to ownership disputes and ineffective management. The waqf certification policy in Indonesia has evolved since the issuance of Government Regulation No. 28 of 1977, with various regulations released by the government to expedite the registration and certification process of waqf land. This study aims to identify the challenges and opportunities within the waqf certification policy and provide recommendations for more efficient policy development towards sustainable development. The findings indicate that despite existing barriers in the certification process, there are also opportunities to improve waqf management through collaboration among institutions and increased public awareness regarding the importance of certification